Kebijakan Pemerintah Daerah dalam Pemenuhan Hak Atas Kesehatan bagi Masyarakat Miskin di Provinsi Sulawesi Selatan - Firdaus Firdaus (Jurnal HAM, 2014)
Health can be defined as a good and perfect condition physically, mentally and socially, hence cannot just be assumed as a condition of physical illness or infirmity. The right to health is guaranteed under Article 28 H (1) and Article 34 (3) of the fourth Amendment of the 1945 Constitution. This right is also universally recognized in various international instruments of human rights law, such as under Article 25 (1) of the UDHR, and Article 12 of the Covenant on ESC rights (economic , social , and cultural). The purpose of this study is to describe the government's policy on health programs for the poor, and also describe several constraints in implementing the program. This study shows that the implementation of the local government's policy concerning health insurance for the poor is yet to be optimal in fulfilling the right to health care for the poor. The health program set up by the local government including JAMKESMAS, Jamkesda, Jampersal, and Non-Quota Jamkesmas, is yet to be maximized and there are still many shortcomings that need to be improved.